Aneurysmal bone cyst of upper cervical spine surgical treatment - Slynko, E. I.; Zolotoverkh, A. M.; Ermolyev, A. I. (Ukrainian Neurosurgical Journal, 2006)
Aneurysmal bone cyst (ABC) is a benign but locally aggressive tumor-like condition. We analyzed the diagnostic data, surgical treatment features and results in 3 observation of ABC СII vertebrae. All patients were performed operations, in one case the extreme lateral approach has been used because the operative risk of vertebral arteries damage while tumor removal. Curettage of the lesion was performed and vertebra defect was reconstructed with anterior titanium mesh. Another two cases were treated from posterior access with fixation. The surgical treatment of ABC should consist of opening the cyst’s cavity, its wide curettage, feeding and draining vessels coagulation, and finally — stabilization. No complications noticed in postoperative period. The neurological signs resolved completely in all patients.